Comparison of four serological assays for the diagnosis of Chlamydia trachomatis in subfertile women - Muvunyi, Claude; Claeys, Laurens; De Sutter, Tineka; De Sutter, Petra; Temmerman, Marleen; Van Renterghem, Lieve; Claeys, Geert; Padalko, Elizaveta (The Journal of Infection in Developing Countries, 2011)
Introduction: Chlamydia antibody testing (CAT) in serum has been introduced as a screening method in the infertility workup. We evaluated the test characteristics of two ELISA tests compared to micro-immunofluorescence tests (MIFs). MIFs are considered the gold standard in the C. trachomatis IgG antibodies detection. We also compared the accuracy of all CAT tests in predicting tubal subfertility, using laparoscopy as a reference. Methodology: Four commercial serological methods were used to analyse 101 serum samples for the presence of C. trachomatis IgG antibodies from patients at the Infertility Clinic of Ghent University Hospital. The diagnostic utility for prediction of tubal infertility of serological methods was evaluated based on patients' medical records. Results: A comparison of the serological assays showed little difference in the major performance characteristics: the sensitivities of all MIFs and ELISAs were 100% for all assays (except the ELISA Vircell, with a sensitivity of 90%), and the specificities ranged from 92% for MIF Ani Labsystems to 98% for the MIF Focus and ELISA Vircell. As compared to laparoscopy data, CAT positivity in subfertile women with tubal damage (n=40) did not significantly differ from that of subfertile women without tubal damage (n=61): Positive predictive values (PPV) of CAT ranged from 53% to 60% and negative predictive values (NPV) ranged from 62% to 64%. Conclusion: evaluated ELISAs are comparable to MIFs in the detection of C. trachomatis IgG antibodies and should be preferred for large serological studies, especially in resource poor settings.